Jews in the Mediterranean diaspora from Alexander to Trajan ( 323 BCE - 117 CE) - Barclay, John M.G. (Edinburgh, Scotland T and T Clark, 1996)
Includes bibliographical references and indexes.
Keywords: Jewish history -- intertestamental period